The effect of prenatal yoga on primigravida trimester II and III in studio qita yoga district south Semarang Indonesia - Priharyanti Wulandari; Dwi Retnaningsih; Euis Aliyah (University of Muhammadiyah Malang, 2018)
A woman who is in pregnancy period often undergoes many changes, whether physical changes or psychological changes. Prenatal Yoga performed during pregnancy can help women focus on the process of labor, exercise to tolerate pain, and changes in stress and anxiety into energy. The purpose of this study was to determine whether there is influence prental yoga on the anxiety level of primigravida mother trimester II and III. This research is pre experiment with one group pre and posttest design. The sampling technique used purposive sampling with the respondents of the research as many as 14 trimester II and III primigravida mothers who had not previously followed prenatal yoga. The statistic test used is Paired Samples T-Test parametric test. Result: This research obtained result of parametric test analysis Paired Samples T-Test p-value = 0,004 <α = 0,05 and value (tcount = 3,726)> (ttable = 1,771) then Ho rejected which means that prenatal yoga have positive effect and significantly to decrease the anxiety level of trimester II and IIImother primigravida. There is prenatal influence of yoa on anxiety level of anxiety of trimester II and III primigravida motherin studio of Qita Yoga South Semarang SubdistrictSemarang City.